A comparative analysis of the theological polemics of Muslim Brotherhood and Salafiyyah - Arikewuyo, Ahmed Nafiu (Penerbit Universiti Kebangsaan Malaysia, 2019)
The experience of the Muslim Ummah in the 19th and 20th centuries has given rise to various revivalist thoughts aimed at reclaiming the lost glory of Islam and returning Muslims to their right position. The Muslim Brotherhood current Salafiyyah groups represent the largest revivalist trend in current time. Despite having the common mission of revitalizing the Ummah, the two trends are always at loggerhead over pressing issues of Islam. Hence, the research focuses on theological polemics as case study for the multitudinous contention between the two trends. Library research methodology was adopted. Findings of the research show that both trends share common fundamental creeds and that the popular theological dichotomy between them is due to various factors namely: the degree of priority attached to creeds, attitude towards equivocal matters of creed such as anthropomorphic status of Allah and lastly theologizing matters which are juristic. The research recommends the needs for the Salafiyyah group to focus on theological training rather than the traditionally theological polemics which was a product of refutation against the evolving heretic sects that are ideologically not existing today.